1990
DOI: 10.1007/bf00265053
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterisation of the benzoate-para-hydroxylase gene (bphA) of Aspergillus niger: A member of a new gene family of the cytochrome P450 superfamily

Abstract: The gene coding for benzoate-para-hydroxylase (bphA) of Aspergillus niger was cloned using differential hybridisation techniques and complementation of mutants deficient in this enzyme activity. The nucleotide sequence of the gene was determined, the presence of two introns was shown and the transcription start and termination sites were determined. The structure of the mRNA upstream from the long open reading frame (ORF) is unusual. It contains two small, overlapping ORFs whose function is unknown. Comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…Our results also revealed that A. oryzae produces ferulic acid in the fermentation mixture, a process enhanced by the addition of aromatic compounds to the medium. The enzymes P450 (monooxygenase), ferulate esterase and xylanase, are also induced by aromatic compounds such as benzoic acid, vanillin and coumaric acid 7,21,32 . In the present study, the level of induction of ferulic acid by other aromatic compounds, including vanillic acid and benzoic acid, was similar to the level induced by vanillin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results also revealed that A. oryzae produces ferulic acid in the fermentation mixture, a process enhanced by the addition of aromatic compounds to the medium. The enzymes P450 (monooxygenase), ferulate esterase and xylanase, are also induced by aromatic compounds such as benzoic acid, vanillin and coumaric acid 7,21,32 . In the present study, the level of induction of ferulic acid by other aromatic compounds, including vanillic acid and benzoic acid, was similar to the level induced by vanillin (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Aromatic compounds induce production of enzymes such as P450, xylase and ferulate esterase 7,21,32 . Vanillin (formed from ferulic acid) and p-coumaric acid are two aromatic compounds that are structurally very similar to ferulic acid 7,11 .…”
Section: Induction Of Ferulic Acid By Aromatic Compoundsmentioning
confidence: 99%
“…In addition to phacA, four stc genes of the A. nidulans sterigmatocystin biosynthetic cluster encode CYP enzymes (24). The closely related organism A. niger has a very specific benzoate-4 hydroxylase enzyme, encoded by the bphA gene (25). Notably, PhacA and BphA each define a new CYP family, suggesting that metabolically versatile saprophytic fungi may represent an as yet unexplored source of variability for CYP enzymes catalyzing novel metabolic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC of benzoic acid required to inhibit spore germination by A. niger was, as expected since benzoic acid is not a PadA1 substrate, identical in both the mutant and the reference strains (AXP8-1) ( Table 1). The degradation of benzoic acid by A. niger and other fungi has been well documented (18)(19)(20)22) and differs in mechanism from that for breakdown of sorbic and cinnamic acids.…”
mentioning
confidence: 99%